The Impact of The Semi-Military Cadetship Model on Religious Character of Vocational High School Students - Awalia Rina Rahwamati, Muh. Nur Rochim Maksum, Triono Ali Mustofa (Kariman: Jurnal Pendidikan Keislaman, 2025)
Vocational education aims to produce graduates who are not only skilled but also have character, one of which is through the implementation of a model of discipline. This study aims to analyze the impact of the semi-military cadetship model on the formation of religious character of vocational school students. Based on a qualitative descriptive paradigm, this research uses a field study method with data collection techniques in the form of interviews and observations. The results showed that the semi-military cadetship model has a significant influence in shaping students' religious character. This connection can be seen from how the versatility routine, such as the habituation of structured worship and the cultivation of responsibility is in line with religious values. The semi-military cadetship model acts as a practical instrument that accustoms students to positive moral behavior which in turn strengthens the foundation of their religious character. Analysis with Islamic education theories, such as Tarbiyah, Ta'lim, and Ta'dib shows that this model is effective in fostering students holistically physically, mentally and spiritually. The model not only forms obedience, but also encourages the internalization of religious values, thus producing graduates who are not only disciplined and competent, but also have integrity and noble morals.